(untitled) (Eurasian Journal of Ecology, 2024)
The article analyzes the current species composition of the fauna and bird population of the city of Kostanay in Northern Kazakhstan in the winter and autumn periods. In urban landscapes characterized by high dynamics of environmental transformation, the reasons for the increase in the number of synanthropic bird species have been identified. This pattern has not been studied for the considered territory of the cities of Northern Kazakhstan. Based on the data obtained, the areas and habitats in the urban ecosystem of Kostanay and the routes of movement in the urban environment were assessed, and the species and quantitative composition of birds was analyzed. The work reflects an analytical manner, which clearly shows that with the emergence of new urban parts, as well as a qualitative change in the built-up area, there is a change in the boundaries of the habitat of many species and their migration processes. The landscapes included in the study represent areas of one-story and multi-story buildings, new city parks on the banks of the Tobyl River. The leading species in each landscape are identified and the factors leading to a reduction in the number of species are listed. It is noted that for the studied urban ecosystem of Kostanay there is no historical data on the state of ornithocomplexes. The results of this study will serve as the basis for further work to describe the processes of change in the avifauna and bird population that may occur in the future with the transformation of the factorial component of the urban environment. Key words: ornithocomplexes, biodiversity, Northern Kazakhstan, Kostanay, current state.